Parkinsonism in Inherited Metabolic Disorders: Key Considerations and Major Features - Limphaibool, Nattakarn; Iwanowski, Piotr; Holstad, Marte Johanne Veilemand; Perkowska, Katarzyna (Frontiers in Neurology, 2018)
Parkinson’s Disease (PD) is a common neurodegenerative disorder manifesting as reduced facilitation of voluntary movements. Extensive research over recent decades has expanded our insights into the pathogenesis of the disease, where PD is indicated to result from multifactorial etiological factors involving environmental contributions in genetically predisposed individuals. There has been considerable interest in the association between neurological manifestations in PD and in inherited metabolic disorders (IMDs), which are genetic disorders characterized by a deficient activity in the pathways of intermediary metabolism leading to multiple-system manifestations. In addition to the parallel in various clinical features, there is increasing evidence for the notion that genetic mutations underlying IMDs may increase the risk of PD development. This review highlights the recent advances in parkinsonism in patients with IMDs, with the primary objective to improve the understanding of the overlapping pathogenic pathways and clinical presentations in both disorders. We discuss the genetic convergence and disruptions in biochemical mechanisms which may point to clues surrounding pathogenesis-targeted treatment and other promising therapeutic strategies in the future.